2 The multi-physics automated reconfigurable separation (MARS®) system provides high purity, high recovery and high throughput enrichment of immune cells for immunotherapy. (10th December 2020) - Yu, Liping; Schneider, Gregory; Wang, Alice
Abstract : Background: Immunotherapies have proven to be a potent disruptor of cancer. Large quantities of purified lymphocytes are needed for expansion and downstream manipulation. This purification step has proven to be a major bottleneck for a streamlined cell production process and will only worsen as CAR-T cell therapies move into the clinic. 1 2 In particular, autologous CAR-T cell therapies directly from cancer patients frequently undergoing existing therapies will require a cell purification technique that provides high recovery, high purity, and high throughput, while being gentle on the cells to ensure downstream efficacy. We present here an integrated system based on multiple physics principles with built-in technologies to achieve cell purification, concentration, and target cell isolation with high recovery and purity at an unprecedented sample flow rate. This platform – the Multi-physics Automated Reconfigurable Separation (MARS®) system – combines novel acoustic cell processing and in-flow immuno-magnetic separation technologies with automation of the entire purification workflow for downstream cellular growth, modification, and analysis prior to being administered to patients. Methods: As a fully automated system, the MARS® system can isolate T-cells with high purity from lysed whole blood in as little as 11 minutes with up to 98% recovery and 98% viability without the need for Ficoll or centrifugation. The process is scalable to 10ML of blood, with complete purification requiring 1 hour. The system is designed to fit into a culture hood for sterile cell handling and has been used to isolate T-cells for expansion for downstream T – cell uses. Results: The tunable microfluidic cell processor is a functional module capable of washing and concentrating various sample types including all white blood cell types from whole blood, bone marrow, and apheresis. Additional uses for thawed frozen PBMC, cultured cells and solid tumor dissociation have also been demonstrated. Comparing with conventional centrifugation process, cell preparation by MARS has demonstrated high level of debris removal (>97%), minimal cell loss (> 90% recovery) and high cell viability with full automation. MARS is the first-to-market fully automated system to integrate sample preparation and cell isolation into a single platform and is designed to be a versatile tool for downstream cell analysis workflows. Conclusions: MARS is the first to market automatic sample preparation system and is designed to be a versatile tool for downstream cell analysis platforms. The MARS® system is an ideal instrument to prepare CAR-T cells due to its ability to isolate and purify these cells from whole blood with high viability in a completely automated process. References: https://medcitynews.com/2018/10/car-t-therapies-face-logistical-bottleneck-as-market-set-to-see-major-growth/ https://www.statnews.com/2018/07/17/car-t-bottleneck-cell-collection-centers-feel-crunch/